MODEL MONITORING DAN EVALUASI PROGRAM KOMUNIKASI PADA USAHA WARALABA DE CHICK FRIED CHICKEN - Deli Luthfi Rahman (ADISAM PUBLISHER, 2025)
The rising trend of fried chicken culinary businesses has driven the emergence of various local partnership-based brands, such as De Chick Fried Chicken. This study aims to examine the implementation of monitoring and evaluation models in De Chick’s internal and external communication programs. The research employed a qualitative descriptive method through observation, interviews, and documentation. The findings indicate that De Chick applies both formative and summative evaluation models in its communication programs, including daily briefings and monthly meetings. Formative evaluation is conducted during program implementation, while summative evaluation is used to assess outcomes and make strategic decisions. The discussion reveals that internal communication effectively maintains operational coordination, whereas external communication fosters relationships with partners, sponsors, and consumers. In conclusion, the monitoring and evaluation of communication programs significantly contribute to De Chick’s growth and serve as a foundation for sustainable business decision-making